You May Call Me Professor: Professor Form of Address in Email Communication and College Student Reactions to Not Knowing What to Call Their Professors - Grace M. Hildenbrand; Evan K. Perrault; Taylor M. Devine (Central States Communication Association, 2020)
This experimental study tested whether a professor's form of address (FOA) and email signature influenced students' perceptions of the professor's credibility, approachability, and likability. Guided by communication accommodation theory, the study investigated the likelihood that students would reciprocate a professor's FOA in email communication. Participants were randomly assigned to one of seven conditions varying by professor FOA (doctor, professor, first name) and email signature (present or not), with a signature only control condition. Results indicated students were more likely to reciprocate the FOA when an email signature was not present. Open-ended responses suggested students perceive instructors more positively when instructors specify a FOA and feel anxious and uncertain when professors do not specify a FOA.